A colonic duplication cyst causing bowel ischaemia in a 74-year-old lady - Fenelon, Christopher (J Surg Case Rep, 2016)
Colonic duplication cysts are rare congenital malformations that predominantly present before the age of 2 years. We report the case of a 74-year-old lady who presented with sudden onset abdominal pain. A computed tomography scan noted a calcified structure adjacent to abnormal loops of bowel. Intraoperative findings revealed an ischaemic loop of small bowel wrapped around a mass in the mesentery adjacent to the sigmoid colon. Final histology revealed a colonic duplication cyst. Colonic duplication cysts are rare entities that most commonly cause obstruction or perforation. We present the very rare case of a colonic duplication cyst causing bowel ischaemia in an elderly female.